Video distortion measurement using psnr in wavelet domain - Mok, Y.L (Universiti Malaysia Sarawak, UNIMAS, 2010)
With the advancement of digital imaging, video coding algorithms that has good performance is important for producing videos in high quality. Objective video quality analysis can improve the video coding algorithms. In this thesis, a new objective method for distortion measurement of videos is proposed. The distortion measurement is based on videos in wavelet domain. The test videos used in the project are test videos provided by Laboratory for Image and Video Engineering (LIVE) video database. 2D Cohen-Daubechies-Feauveau (CDF) 9/7 wavelet is applied to the video frames. The objective measurement used in this project is Peak Signal-to-Noise Ratio (PSNR). The project calculates the differences of the reference video and the distorted video in wavelet domain, by implementing PSNR values as the objective measurement. An overall PSNR score for a distorted video is also determined from the analysis. PSNR values of the video in wavelet domain are compared to the PSNR values of the videos in spatial domain. Performance, reliability, and consistency of the proposed video distortion measurement scheme are also analysed in this thesis by comparison to the PSNR values of videos in spatial domain. The PSNR values are calculated using MATLAB and the values are exported to Microsoft Excel to perform analysis.